Pengaruh Bermain Hopschotch Modification Terhadap Perkembangan Kognitif Anak Kelompok A Di Ra Al-Azhar Menganti - Jauharotun Nafi’ah; Muhammad Mahfud (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
Based on preliminary observations made by researchers at RA Al-Azhar Menganti Gresik, it can be concluded that children's cognitive abilities in recognizing numbers, recognizing geometry, and children's ability to recognize colors are still not good enough. The formulation of the problem in this study is whether playing hopschotch modification has an effect on the cognitive development of group A children at RA Al-Azhar Menganti Gresik. This type of research is quantitative experimental method with Pre-Experimental Design which uses a one group pretest-posttest design approach consisting of pretest, treatment, and posttest. This study uses a non-probabilty sampling technique with a saturated sampling method. The sample in this study were all students and students of group A at RA Al-Azhar Menganti Gresik. The results showed that the average value of 38.35 was obtained from the cognitive abilities of children before playing hopschotch modification. Then the average value of 54.59 was obtained from the child's cognitive ability after playing hopschotch modification. Then supported by the results of nonparametric statistics with the Wilcoxon Signed Rank Test, the Asymp.Sig (2-tailed) value is 0.00. It can be concluded that Asymp.Sig (2-tailed) is 0.00 < 0.05, then Ho is rejected and Ha is accepted. Based on the results of this study, it can be stated that playing hopschotch modification has an effect on the cognitive development of group A children at RA Al-Azhar Menganti Gresik.